Mangayaw and Banyaga Moro wars, China trade, and the shifting hermeneutics of piracy, slavery, and ethno-nationalism - Casiño, Eric S. (2016)
In Majul's "Moro Wars" construct, the cycle of piratical raids against Spanish-held territories in the Philippines is recast as counter-attacks in defense of Islam and Moro areas, in retaliation for Spanish attempts to conquer Mindanao and Sulu. By reading them through the lens of religious jihad and of a postulated patriotism, he hoped to connect Moro history with anticolonial, nationalist historiography of mainstream Filipino historians. His reinterpretation of Moro history has inspired later Moro ideologues to proclaim an imagined Moro pre-nationalism that is parallel to or aligned with later Filipino nationalism. Other historians, armed with many more historical facts than what Majul used, do not support his jihad theory behind the Moro Wars. James Warren, in his book The Sulu Zone, has provided a wider array of piratical and slavery-based economic practices and religious zealotry. Moro traders in the Sulu Zone did not oppose but collaborated with British commercial imperialists in opening up the China market that had a huge demand for Sulu Zone marine and forest products. Increased demand for them drove Moro sultans and datus to engage in systematic, regionwide slave-raiding expeditions, to export to China. Thus, Majul's argument on the anti-Hispanic and religious basis of the Moro Wars has become hardly tenable in the face of more facts and newer interpretations.
Keywords: Jihad -- Moral and ethical aspects; Slavery -- Sociological aspects; Sulu archipelago -- Historiography; Sulu (Mindanao) -- History